Mediation as a Profession: Ethical Models, Principles and Challenges - Tamta Margvelashvili (Alternative Dispute Resolution Yearbook, 2017)
The paper discusses idea and importance of mediation, its professional assignment and value, discusses in more details main issues of mediation ethics, its established models which are still developing and needs perfecting by combining practice and theory. In addition, based on legislative regulations of different countries, discussing mediation codes of ethics and their comparison in the paper, we shall define the basic principles of mediation, main ethical challenges of mediator’s activities which need reaction on time on national and international level. As a result, by analyzing problems existing in mediation ethics sphere, ethical challenges will be differentiated and it will be possible to talk about their solution. This will be the step forward for developing mediation practice and theory.